NIMG-32. COMPARISON OF L-METHYL-11C-METHIONINE POSITRON EMISSION TOMOGRAPHY WITH MAGNETIC RESONANCE SPECTROSCOPY IN DETECTING NEWLY DIAGNOSED GLIOMA. (5th November 2018) - Kebir, Sied; Lazaridis, Lazaros; Weber, Manuel; Deuschl, Cornelius; Stoppek, Ann-Kathrin; Schmidt, Teresa; Boehm, Judith; Moenninghoff, Christoph; Scheffler, Björn; Keyvani, Kathy; Pierscianek, Daniela; Sure, Ulrich; et al.
Abstract: BACKGROUND: Amino acid positron emission tomography (PET) and magnetic resonance spectroscopy (MRS) are at the forefront of non-invasive imaging techniques used for detection and subtyping of glioma-suspicious lesions. No reported studies so far attempted to compare those techniques performed during one single preoperative session in their ability to predict glioma subtypes. METHODS: Twenty patients with histologically confirmed newly diagnosed glioma underwent preoperative MET PET and MRS during one single diagnostic session. According to the molecular portfolio and histopathological diagnosis, patients were subdivided in isocitrate dehydrogenase (IDH) wildtype glioblastoma (GBM), IDH wildtype grade II/III glioma (IDHW), IDH mutant grade II/III glioma without 1p/19q codeletion (IDHMnc) and with 1p/19q codeletion (IDHMcod). Maximum tumor-to-brain ratio (TBRmax), creatine, choline and N-acetyl aspartate (NAA) peaks were correlated with postoperative histopathological tumor diagnoses. To gain generalizable implications from our data we subdivided the full study cohort into a development and validation subcohort. A support vector machine model was fitted to the development subcohort and evaluated on the validation subcohort. Receiver operating characteristic (ROC) curve with area under the curve (AUC) as metric served to assess model performance. RESULTS: TBRmax was highest in GBM patients (4.18), followed by IDHW patients (3.04). The latter TBRmax values were higher compared to those in IDHMnc patients (1.95) and in IDHMcod patients (2.79). MRS marker distribution showed no clear trend. ROC analysis revealed TBRmax to be the best performing parameter in identifying IDH status (AUC: 0.67) and all spectroscopy markers combined in identifying glioma subgroups (AUC: 0.68). CONCLUSIONS: MET PET and MRS bear limited potential in glioma subgrouping. However, MET PET appears to be slightly superior in differentiating IDH status. Investigation in a larger cohort is required to draw definite conclusions.